2015
DOI: 10.1101/023168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenomic species tree estimation in the presence of incomplete lineage sorting and horizontal gene transfer

Abstract: Background: Species tree estimation is challenged by gene tree heterogeneity resulting from biological processes such as duplication and loss, hybridization, incomplete lineage sorting (ILS), and horizontal gene transfer (HGT). Mathematical theory about reconstructing species trees in the presence of HGT alone or ILS alone suggests that quartet-based species tree methods (known to be statistically consistent under ILS, or under bounded amounts of HGT) might be effective techniques for estimating species trees … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…While a discussion of the associated challenges of concatenation and MSC methods is well beyond the scope of this work, a strong consensus exists in the literature in favor of using MSC methods to study shallow evolutionary relationships. More specifically, simulations suggest that MSC methods are better than concatenation methods in recovering highly accurate species relationships under ILS levels (Edwards et al, ; Degnan & Rosenberg, ; Davidson, Vachaspati, Mirarab, & Warnow, ; Mirarab, Bayzid, & Warnow, ). The latter approach may then be especially important for taxa that underwent relatively rapid divergence, such as Callithrix , and possess a recent tree root and associated shallow species trees usually typified by higher levels of ILS (Degnan & Rosenberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…While a discussion of the associated challenges of concatenation and MSC methods is well beyond the scope of this work, a strong consensus exists in the literature in favor of using MSC methods to study shallow evolutionary relationships. More specifically, simulations suggest that MSC methods are better than concatenation methods in recovering highly accurate species relationships under ILS levels (Edwards et al, ; Degnan & Rosenberg, ; Davidson, Vachaspati, Mirarab, & Warnow, ; Mirarab, Bayzid, & Warnow, ). The latter approach may then be especially important for taxa that underwent relatively rapid divergence, such as Callithrix , and possess a recent tree root and associated shallow species trees usually typified by higher levels of ILS (Degnan & Rosenberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [56] examined the effect of HGT on the pseudolikelihood method MP-EST and predicted that, mathematically, species tree branch lengths may be biased by HGT but that topologies were fairly robust. Davidson et al [108] found that quartetbased methods, such as ASTRAL-II, were fairly robust to HGT in the presence of ILS. Removal of genes suspected to be transferred via HGT prior to species tree analysis would be warranted; however, some methods to detect such events rely both on having the true species tree already in hand and also on the absence of other mechanisms causing gene tree discordance [109][110][111][112].…”
Section: Horizontal Gene Transfermentioning
confidence: 99%
“…The gene trees with the highest likelihoods from the RaxML analyses on each locus were combined and used as the input for analysis in ASTRAL-II. This method finds the tree that maximizes the number of induced quartet trees in the set of gene trees that are shared by the species tree and has shown to be accurate, even in the presence of incomplete lineage sorting and horizontal gene transfer (Chou et al, 2015;Davidson et al, 2015). We used the heuristic search and multi-locus bootstrapping functions for phylogenetic reconstruction.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%